العلاقة بين الوحدة والكثرة من طاليس إلى سقراط - محمد بتول حكمت (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
يناقش هذا البحث تفسير الوجود عند الفلاسفة اليونان الأوائل من طاليس إلى سقراط انطلاقاً من دراسة العلاقة بين الوحدة والكثرة وتفسيرها في الفلسفة اليونانية، الذي اعتمد على الابتعاد عن التسليم الذي اتصفت به الأسطورة ليعتمد العقل في البحث عن حقيقة هذا الوجود، الذي جعلته الفلسفة منذ ولادتها أساساً في البحث عن الحقيقة أينما كانت. This research discusses the interpretation of existence by the early Greek philosophers from Thales to Socrates based on the study of the relationship between the unity and multiplicity; and its interpretation in the Greek philosophy. Such interpretation depends on keeping far from the belief that Mythology depended on. Rather, it relies on the mind to seek the reality of this existence that philosophy-from its cradle-held it the basis for seeking reality wherever it exists.